Real time monitoring of surveillance CCTV - Nadhirah, Ali (2010)
Traditionally the surveillance monitoring system is done in the larger room and by a mount of manpower. But nowadays, monitoring surveillance system can be done through online network. This type of monitoring is more time consuming and can reduce the manpower. Moreover, it gives the user flexibility to monitor their properties where ever they want as long as they have the internet network. Either than that, this project also manage to detect the movement in the video, this will be a greater help to the user to observe their properties. In the end, this project is not only can reduce the cost for monitoring but also give advantages to the user